Insulin-like growth factor levels in cord blood, birth weight and breast cancer risk - Lagiou, P (Nature Publishing Group, 2009)
Breast cancer incidence and birth weight are higher among Caucasian than Asian women, and birth size has been positively associated with breast cancer risk. Pregnancy hormone levels, however, have been generally lower in Caucasian than Asian women. We studied components of the insulin-like growth factor (IGF) system in cord blood from 92 singleton babies born in Boston, USA, and 110 born in Shanghai, China, in 1994–1995. Cord blood IGF-1 was significantly higher among Caucasian compared with Chinese babies (P<10(−6)). The opposite was noted for IGF-2 (P∼10(−4)). IGF-1 was significantly positively associated with birth weight and birth length in Boston, but not Shanghai. In contrast, stronger positive, though statistically non-significant, associations of IGF-2 with birth size were only evident in Shanghai. The associations of birth weight and birth length were positive and significant in taller women (for IGF-1 in Boston P∼0.003 and 0.03, respectively; for IGF-2 in Shanghai P∼0.05 and ∼0.04, respectively), among whom maternal anthropometry does not exercise strong constraints in foetal growth. The documentation of higher cord blood levels of IGF-1, a principal growth hormone that does not cross the placenta, among Caucasian than in Asian newborns is concordant with breast cancer incidence in these populations.